2017
DOI: 10.12659/msm.904486
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Expression of Vimentin Predicts the Clinical Outcome of Stage II Colorectal Cancer for High-Risk Patients

Abstract: BackgroundIncreased expression of vimentin in tissue samples from patients with colorectal cancer (CRC) has been previously demonstrated, but its prognostic significance remains controversial, and the clinical significance for patients with stage II CRC is still unknown. The aim of this study was to evaluate the expression of vimentin in CRC and its potential prognostic significance.Material/MethodsWe analyzed vimentin expression in 203 CRC tissue samples from patients with stage II cancer using immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…27 Molecularly, the EMT phenotype is characterized by downregulation of epithelial markers (E-cadherin) and upregulation of mesenchymal markers (N-cadherin, Vimentin and snail). 28,29 In hepatocellular carcinoma, c-Myb functions as a target of long non-coding RNA downregulated in hepatocellular carcinoma (DRHC) to promote the EMT phenotype through the MEK/ERK signaling pathway. 30 c-Myb could also cooperate with transforming growth factor beta (TGF-β) to enhance the EMT phenotype of estrogen(+) breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…27 Molecularly, the EMT phenotype is characterized by downregulation of epithelial markers (E-cadherin) and upregulation of mesenchymal markers (N-cadherin, Vimentin and snail). 28,29 In hepatocellular carcinoma, c-Myb functions as a target of long non-coding RNA downregulated in hepatocellular carcinoma (DRHC) to promote the EMT phenotype through the MEK/ERK signaling pathway. 30 c-Myb could also cooperate with transforming growth factor beta (TGF-β) to enhance the EMT phenotype of estrogen(+) breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have revealed high vimentin expression as a negative prognostic factor in human neoplasms. In the case of colorectal cancer, it was shown that both tumor cell expression and tumor stroma expression were associated with poor patient prognosis [19,20,23]. In a meta-analysis by Du et al, vimentin expression indicated a shortened OS and disease-free survival (DFS), lymph node metastases, and a higher TNM stage of colorectal cancer patients [23].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, our study is the first to report vimentin expression in the stroma of the ovarian neoplasm. We did identify studies showing that a poorer prognosis is related to stromal vimentin expression;but those studies concerned patients with colorectal and prostate cancers [20,29]. The tumor stroma mainly consists of resident fibroblasts, endothelial cells, pericytes, leukocytes, and extra-cellular matrix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical stage of disease is an indicator of prognosis for patients with CRC. Clinical stage I–II is considered early stage, while clinical stage III–IV is considered to be late stage (35,36).…”
Section: Resultsmentioning
confidence: 99%